To subtract the fractions \( \frac{2}{3} - \frac{3}{4} \), we first need to find a common denominator. The denominators are 3 and 4. The least common multiple (LCM) of 3 and 4 is 12.
Now, we convert each fraction to have a denominator of 12:
\[ \frac{2}{3} = \frac{2 \times 4}{3 \times 4} = \frac{8}{12} \]
\[ \frac{3}{4} = \frac{3 \times 3}{4 \times 3} = \frac{9}{12} \]
Now we can subtract the two fractions:
\[ \frac{8}{12} - \frac{9}{12} = \frac{8 - 9}{12} = \frac{-1}{12} \]
So,
\[ \frac{2}{3} - \frac{3}{4} = \frac{-1}{12} \]